International knowledge flows and economic performance: An introductory survey of the evidence - Giorgio Barba Navaretti; David Tarr (Fondazione Eni Enrico Mattei (FEEM), 2000)
The empirical analysis of the micro links between trade and knowledge diffusion allows us to distinguish among the key predictions of the theoretical literature on endogenous growth. This literature postulates that total factor productivity (TFP) is higher when trade gives access to a wider or more sophisticated range of technologies. The papers reviewed here find considerable evidence that imported technologies positively affect TFP in the importing countries, particularly in developing ones and when technologies are acquired by way of imports of intermediates . It also provides some support for the models that argue that exporting is an efficient learning channel. The role of foreign direct investment is more mixed, likely helping the economy but hurting domestic competitors. Relative factor and machinery costs, skill and technology endowments affect the choice of imported technologies. Although the access to foreign technologies has a positive impact on developing countries' TFP, overall, these countries are shown to purchase older and simpler. But governments' attempts of limiting or guiding technology selection are likely to have a negative effect on growth, because they force producers either to choose sophisticated technologies they are unable to use or they prevent them from getting the most appropriate and efficient technologies. Rather, policies aimed at promoting technological development should strengthen the absorptive capacity of importing countries by addressing the relationship of complementarity between human and physical capital.
Keywords: O12; O30; F10; 330; Knowledge flows; technological diffusion; spillovers; total factor productivity; microeconomics of economic growth; RJV's; international trade; foreign direct investments; Wissenstransfer; Technologietransfer; Lernprozess; Internationale Wirtschaft; Direktinvestition; Produktivität; Wirtschaftswachstum; Theorie